PENGARUH PENGETAHUAN WAJIB PAJAK, KESADARAN WAJIB PAJAK, LINGKUNGAN SOSIAL, SISTEM SAMSAT DRIVE THRU DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN MEMBAYAR PAJAK KENDARAAN BERMOTOR DI WILAYAH LOMBOK TIMUR - Erisfiana Erisfiana; Akhmad Saufi; Lalu M. Furkan (Distribusi - Journal of Management and Business, 2020)
This study discusses the variables of taxpayer knowledge, awareness of taxpayers, social environment, SAMSAT Drive Thru system, and quality of service to taxpayer decisions in vehicle tax payments in the East Lombok region. The sample used is the vehicle taxpayer who was moved in East Lombok Regency and taken as many as 100 respondents using the Simple Random Sampling method. The results showed that taxpayers, taxpayer awareness, and the SAMSAT Driving system through positive and significant decisions on transportation tax payments in the East Lombok region, while the social environment and service quality were not significant in influencing taxpayer decisions. The government in this regard (BAPPENDA) can provide complete and scheduled outreach and education on tax regulations that require taxpayers in every environment, because related to the social environment, taxpayers are according to categories that are less conducive. In addition, BAPPENDA must improve its services by providing training and seminars for its employees.